2020
DOI: 10.1186/s13046-020-01625-8
|View full text |Cite
|
Sign up to set email alerts
|

SRSF10 inhibits biogenesis of circ-ATXN1 to regulate glioma angiogenesis via miR-526b-3p/MMP2 pathway

Abstract: Background: Angiogenesis plays an important role in the progress of glioma. RNA-binding proteins (RBPs) and circular RNAs (circRNAs), dysregulated in various tumors, have been verified to mediate diverse biological behaviors including angiogenesis. Methods: Quantitative real-time PCR (qRT-PCR) and western blot were performed to detect the expression of SRSF10, circ-ATXN1, miR-526b-3p, and MMP2/VEGFA. The potential function of SRSF10/circ-ATXN1/miR-526b-3p axis in glioma-associated endothelial cells (GECs) angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 54 publications
1
37
0
Order By: Relevance
“…Increasing evidence has shown that circRNAs, such as circASH2L (Chen et al, 2019), circHIPK3 (Wang et al, 2019b), circMET (Pei et al, 2020), circATXN1 (Liu X. et al, 2020), circZNF566 , circFMN2 (Shan et al, 2020), circCYFIP2 (Lin et al, 2020), and circWHSC1 (Zong et al, 2019), have essential functions in cancer biology and are potential biomarkers and treatment targets. We determined the expression of the eight star circRNAs in ovarian cancer and found that circASH2L was the only one expressed differently in our samples ( Figure 1A).…”
Section: Circash2l Expression Is Elevated In Ovarian Cancer Tissues Amentioning
confidence: 99%
“…Increasing evidence has shown that circRNAs, such as circASH2L (Chen et al, 2019), circHIPK3 (Wang et al, 2019b), circMET (Pei et al, 2020), circATXN1 (Liu X. et al, 2020), circZNF566 , circFMN2 (Shan et al, 2020), circCYFIP2 (Lin et al, 2020), and circWHSC1 (Zong et al, 2019), have essential functions in cancer biology and are potential biomarkers and treatment targets. We determined the expression of the eight star circRNAs in ovarian cancer and found that circASH2L was the only one expressed differently in our samples ( Figure 1A).…”
Section: Circash2l Expression Is Elevated In Ovarian Cancer Tissues Amentioning
confidence: 99%
“…Recent reports revealed that circRNAs exert their biological functions mainly relying on the miRNA sponging ( Hansen et al, 2011 , 2013 ). Besides, circRNAs could also play a role in interacting with RNA binding proteins (RBPs) ( Liu et al, 2020 ). In PCa, circRNAs, such as, circ_0007494 and circFMN2, have been recognized to function as competing endogenous RNAs (ceRNAs) to relieve the inhibition of miRNA targets ( Shan et al, 2020 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As reported in the literature, MMP2 and MMP9 are closely related to vasculogenic mimicry formation in gliomas (42). Thus, by regulating the MMP2-related pathway, glioma angiogenesis could be inhibited (43). Meanwhile, the regulation of MMP9 activity was shown to be correlated with tumor cell invasion (44).…”
Section: Discussionmentioning
confidence: 84%